Human resources administration for educational leaders - Norton, M. Scott (SAGE, 2008)
A comprehensive and research-based text detailing the important relationship between school administration and human resources administration.“The author provides [students] with specific strategies for navigating the treacherous waters of personnel selection, development, retention, and removal. I wish I had the book when I began my work as Director of Personnel.”—Zach Kelehear University of South CarolinaHuman Resources Administration for Educational Leaders balances theory and pedagogy to demonstrate the historical evolution of the human resources function in education, the link between human resources and organizational effectiveness, and the new trends in human resources accountability.Key Features and Benefits:Accompanied by High-Quality AncillariesInstructors' Resources on CD-ROM includes a test bank, sample syllabi, PowerPoint slide presentations, and more. Contact SAGE to request your copy. Meet the author!